(untitled) (Journal of Scientific Research, 2014)
Low birth weight in new born is major reason of neonatal deaths resulting in severe short term and long term effect on babies. Descriptive study conducted with the help of questionnaires to study factors contributing to deliver low birth weight babies, investigating interrelationships among different factors effecting LBW and increasing awareness of LBW among expecting mothers. Data was collected from June to September 2013. A total of 140 questionnaires were filled from three tertiary care hospitals after taking informed consent form participants. Outcomes of the study included that maternal BMI, maternal education, malnutrition, and infections and diseases during pregnancy had positive impact on delivering LBW babies. Mothers with familial vertical history of LBW, inter-pregnancy interval of less than one year and those having previous LBW babies were more likely to deliver LBW baby. Mothers belonging to higher socioeconomic class, those using multivitamins and folic acid during pregnancy had less chances of having LBW. Keywords: Birth weight; Preterm birth; Growth retardation; Gestational age, Inter-pregnancy interval. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17090 J. Sci. Res. 6 (2), 387-394 (2014)